Analysis of the Supervision of the Head of the Room at the Ahmad Dahlan Muhammadiyah Hospital on the Performance of Nurses - Emeylian Dhea Prisantika; Anita Restu Korbaffo (Open Access Health Scientific Journal, 2020)
Background: The problem of performance in hospitals is the center of attention because it involves the efficiency and effectiveness of human resources in achieving the goals and vision of the organization. Many factors affect performance, including supervisory factors from superiors which ultimately have an impact on overall performance results as an organization. Method: The design of this research is correlational with the population of all nurses in the inpatient ward of Muhammadiyah Hospital Ahmad Dahlan Kediri totaling 67 people. The sample is part of the population with a Stratified Random Sampling technique of 57 respondents. The data that has been collected is processed with the Spearman Rho statistical test with a significance of = 0.05. Results: The results of the analysis of the spearman rho test obtained a p-value = 0.000 which is less than the value of (0.05), it can be concluded that H0 is rejected, meaning that there is a relationship between the supervision of the head of the room and the performance of nurses at Ahmad Dahlan Hospital, Kediri. Conclusion: The results of this study also prove that supervision is able to improve the performance of nurses because when carrying out supervision there are certain actions that are evaluated by the head of the room against nurses, so that if the evaluation is corrected by nurses, it will be able to improve the performance of nurses